PROPRIOCEPTION AND MOTOR KINESTHESIA: REAL GAINS WITH THE INTENSIVE SPEECH THERAPY AT THERASUIT - Guedes, Cecília Cavalcanti Bernardo; do Vale, Lorena Grace Alves (Seven Editora, 2025)
This article deals with important issues in the speech therapy treatment of children with communication problems due to significant global neuropsychomotor developmental disorders using the Intensive Speech Therapy at Therasuit (ISTT) program. The aim of the research is to find evidence that ISTT shows significant results in terms of gains in proprioception and kinesthesia in children undergoing specialized speech therapy. In continuity with the ISTT program carried out and published in a scientific journal "SLP in the therasuit method: Innovations and contributions to children's rehabilitation", we will show results in terms of the proprioceptive and synesthetic aspects of speech in a group of patients undergoing speech therapy. The scientific methodology is a longitudinal case study of a group of twelve children who have been followed up for over three years, one and a half of which using the ISTT protocol. After analyzing the results, we concluded that the gains of the IFT method in speech therapy are relevant when compared to the same period in a control group and we suggest indicating therapy for various cases of speech and language disorders due to the overall clinical improvement.DOI: https://doi.org/10.56238/sevened2025.026-024